2021
DOI: 10.1021/acs.iecr.0c05528
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Spatial Distribution of Active Material on Bifunctional Hydrocracking

Abstract: Bifunctional catalysts are the preferred choice for hydrocracking processes. Ideal hydrocracking performance is defined by quasi-instantaneous (de)hydrogenation reactions over the metal sites and limited acid catalyzed side reactions, particularly the secondary cracking of desired products. Although their performance is heavily determined by the balance in activity between metal and acid sites, the spatial arrangement between both functions also holds a significant influence. Distance represents the simplest m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Hydrocracking, a traditional method to cleave the C−C bond, is usually adopted to produce short-chain hydrocarbons in petroleum refinery. Generally, in this hydro-process of breaking the C−C bond, bifunctional catalysts with both metal and acid active sites, for example, Ni-or Co-modified MoS 2 or WS 2 supported on molecular sieve 11 and Pt supported on Al 2 O 3 , 12 were used before. Recently, we reported a multifunctional Ru/NbOPO 4 catalyst, which could efficiently cleave the C sp2 −C sp3 bond and C−O bond in one-pot conversion of lignin or aromatic plastics to aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrocracking, a traditional method to cleave the C−C bond, is usually adopted to produce short-chain hydrocarbons in petroleum refinery. Generally, in this hydro-process of breaking the C−C bond, bifunctional catalysts with both metal and acid active sites, for example, Ni-or Co-modified MoS 2 or WS 2 supported on molecular sieve 11 and Pt supported on Al 2 O 3 , 12 were used before. Recently, we reported a multifunctional Ru/NbOPO 4 catalyst, which could efficiently cleave the C sp2 −C sp3 bond and C−O bond in one-pot conversion of lignin or aromatic plastics to aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrocracking, a traditional method to cleave the C–C bond, is usually adopted to produce short-chain hydrocarbons in petroleum refinery. Generally, in this hydro-process of breaking the C–C bond, bifunctional catalysts with both metal and acid active sites, for example, Ni- or Co-modified MoS 2 or WS 2 supported on molecular sieve and Pt supported on Al 2 O 3 , were used before. Recently, we reported a multifunctional Ru/NbOPO 4 catalyst, which could efficiently cleave the C sp2 –C sp3 bond and C–O bond in one-pot conversion of lignin or aromatic plastics to aromatic hydrocarbons. , In the supported metal catalysts, the metals (Pt, Pd, Ru, Ni, Co) usually play a key role in activating the hydrogen molecule, which is considered to be necessary in hydro-processing. ,, However, Zhang et al reported that ceria with oxygen vacancies (O v ) showed good activity in hydrogenation reactions due to its ability to produce H δ− species via the heterolytic pathway, where the oxygen vacancies played an important role in the formation and stabilization of hydride species (Ce Ov 4+ –H – ) .…”
Section: Introductionmentioning
confidence: 99%
“…In general, “catalytic cracking” refers to cracking on monofunctional acidic catalysts. However, polyolefin hydrocracking occurs on bifunctional catalysts, which comprise hydrogenation/dehydrogenation components (i.e., noble metal Pt and Pd) and a Brønsted acid component (usually zeolite). ,, It is well-known that the distinctive feature of hydrocracking of light hydrocarbons is the ability to promote the yield of saturated products and enhance the isomerization reaction of n -paraffins. Indeed, previous reports confirmed that polyolefin hydrocracking over metal/zeolite catalysts also showed a higher yield of paraffin than of olefins with a higher ratio of iso to normal. For example, Pyra et al looked at the catalytic performance of H-beta (catalytic cracking) and Pd/beta (hydrocracking) in polyolefin conversion . As shown in Figure a, catalytic cracking and hydrocracking showed relatively lower T 50 value than thermal pyrolysis, and the hydrocracking reaction over a Pd/beta catalyst exhibited the lowest T 50 value, indicating that the addition of Pd could further enhance the cracking activity.…”
Section: Metal/zeolite Composites In Catalytic Conversion Of Polyolefinsmentioning
confidence: 99%
“…In addition to the metal type, the distance between metal and acid sites could also affect the hydrocracking of polyolefins. This is because it can influence the diffusion behavior of olefin intermediates; if the metal is near the acid site, the intermediates are confined in the zeolite pores and subject to deep cracking, resulting in a selectivity shift to light products as a result . On the other hand, separating metal and zeolite acid sites could increase the selectivity of heavier products.…”
Section: Metal/zeolite Composites In Catalytic Conversion Of Polyolefinsmentioning
confidence: 99%
“…Hydrocracking, a traditional method to cleave C-C bond, was usually adopted to produce short-chain hydrocarbons in petroleum refinery. Generally, in this hydro-process for breaking C-C bond, bifunctional catalysts with both metal and acid active sites, such as Ni-or Co-modified MoS2 or WS2 supported on molecular sieve 15 and Pt supported on Al2O3, 16 are required. Recently, we reported a multifunctional Ru/NbOPO4 catalyst, which could efficiently cleave Csp2-Csp3 bond and C-O bond in one-pot conversion of lignin to monocyclic hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%